2012
DOI: 10.1097/prs.0b013e31824422a8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Influences of Twins on the Pathogenesis of Craniosynostosis

Abstract: Risk, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…The present study describes the occurrence of isolated craniosynostosis with opposite directed impact on craniofacial growth (scaphocephaly versus oxycephaly) in monozygotic twins and supports the hypothesis proposed previously in other studies (Lajeunie et al, 2005;Butzelaar et al, 2009;Johnson and Wilkie, 2011;Lakin et al, 2012) that a combination of predisposition (genetic factors) and an environmental component (i.e. constraint secondary to twin pregnancy or large fetus) may cause isolated craniosynostosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study describes the occurrence of isolated craniosynostosis with opposite directed impact on craniofacial growth (scaphocephaly versus oxycephaly) in monozygotic twins and supports the hypothesis proposed previously in other studies (Lajeunie et al, 2005;Butzelaar et al, 2009;Johnson and Wilkie, 2011;Lakin et al, 2012) that a combination of predisposition (genetic factors) and an environmental component (i.e. constraint secondary to twin pregnancy or large fetus) may cause isolated craniosynostosis.…”
Section: Discussionsupporting
confidence: 87%
“…A recent meta-analysis by Lakin et al (2012) reviewing the literature of monozygotic and dizygotic twins with isolated craniosynostosis has concluded that craniosynostosis likely results from a combination of genetic and environmental factors. The present study describes the occurrence of isolated craniosynostosis with opposite directed impact on craniofacial growth (scaphocephaly versus oxycephaly) in monozygotic twins and supports the hypothesis proposed previously in other studies (Lajeunie et al, 2005;Butzelaar et al, 2009;Johnson and Wilkie, 2011;Lakin et al, 2012) that a combination of predisposition (genetic factors) and an environmental component (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Although an adverse intrauterine environment may contribute substantially to the origin of many cases of craniosynostosis [1113], this is difficult to prove in the individual patient [14]. Overall, only 2.4% of cases were attributed to a likely secondary cause in the Oxford series.…”
Section: A Current Benchmark For Diagnosismentioning
confidence: 99%
“…Prenatal risk factors, such as maternal thyroid disorders, gestational diabetes, drug use, malnutrition, virus infectious, intrauterine constraint, twin gestation, premature delivery, are associated with craniosynostosis and likely increase the susceptibility in an already genetically predisposed infant [7,[11][12][13][14]. Monochorionic (MC) twins provide exceptional chances to decipher the interplay among genetic and environment in uences in the pathogenesis of premature suture fusion [34]. In our study, the mother of monochorionic twins suffered the majority of risk factors prenatally, however, only the infant with breech presentation and intrauterine growth restriction experienced sagittal craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%